ACCRUAL-BASED ACCOUNTING IN PUBLIC HEALTH CENTER BLUD: ENHANCING FINANCIAL TRANSPARENCY AND ACCOUNTABILITY - Rahmat Zuhdi; Moh Toyyib; Yustin Nur Faizah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study explores the significance and challenges of implementing PSAP 13 accrual in Public Health Center BLUDs. Using a qualitative approach with a phenomenological method, data were collected through in-depth interviews, direct observations, and documentation studies. Triangulation was conducted across sources, techniques, and time to ensure data validity. Therefore, this study found that transitioning from a First Level Health Facility (FKTP) to a BLUD has significantly impacted accounting practices. The adoption of PSAP 13 accrual accounting places a substantial burden on health workers, requiring them to prepare seven financial reports. However, only two of the reports are actively used for decision-making, while the other five serve as mere formalities. Frequent errors occur in recording specific accounts due to limitations in the SIMDA application and a lack of understanding of accrual concepts among human resources. This situation creates stress, anxiety, and frustration, heightened by strict deadlines and audit pressures. Many Public Health Centers struggle with implementation, highlighting unpreparedness and a sense of forced compliance. Furthemore, this study recommends the need for targeted training and system enhancements to support practical accrual-based accounting in BLUDs.